Analysis of water profile at the Bukit Kuang bridge, Kemaman - Farra Intan Syamira, Zulkifli (2019)
Massive development occurs near the river area which resulted in increase in demand of river infrastructure such as bridge. A new replacement bridge crossing the Chukai River called the Bukit Kuang Bridge, Kemaman was opened on 2014. It is important to understand about the hydrology and hydraulic characteristic of the river to ensure the efficiency of the bridge’s design and its safety. Analysis of water profiles were carried out to determine the water levels at the old bridge piers and the new bridge piers. The old bridge had ten piers while for the new bridge has two piers. The new replacement bridge was design to allow ships to pass through. Simulation using the 2013 to 2018 rainfall data as input to HEC-HMS produced peak flows and hydrographs for 5-year, 10-year, 20-year, 50-year and 100-year ARI. Output of HEC-HMS were used in HEC-RAS to determine the water profile for 2,700 meter before and after the bridge piers location. From the analysis at the new bridge piers, the water level at 100-year ARI shall not overflow along the river since the river was deepen to allow ships passing through.